Strategic Approach to Enhance Information Security Awareness at ABC Agency - Hakim, Fandy Husaenul; Hilman, Muhammad Hafizhuddin; Yazid, Setiadi (Ikatan Ahli Informatika Indonesia (IAII), 2025)
Information security awareness (ISA) is crucial to an organization's cybersecurity strategy, particularly since employees are often the last defense against cyberattacks. Despite regular communication on cybersecurity threats, the ABC Agency has not evaluated the level of ISA among its employees, leaving a gap in understanding the effectiveness of its awareness programs. This is critical, as the agency handles highly confidential data that could be at risk of accidental or intentional leaks. The Kruger Approach and the Human Aspect of Information Security Questionnaire (HAIS-Q) were used in this study to measure the ISA levels of employees at the ABC Agency. We employed the Analytic Hierarchy Process (AHP) method to analyze data collected from 86 respondents. The findings indicate that ABC Agency employees demonstrate satisfactory ISA overall. However, the